Effectiveness of montelukast in the treatment of atopic dermatitis - Rahman, ML; Choudhury, AM; Islam, MM (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jan;15(1):85-8The abstract of this article is available on the PubMed website